Cellular Levels of trp RNA-Binding Attenuation Protein in Bacillus subtilis - McCabe, Barbara C. (American Society for Microbiology, 2004)
Expression of the Bacillus subtilis trp genes is negatively regulated by an 11-subunit trp RNA-binding attenuation protein (TRAP), which is activated to bind RNA by binding l-tryptophan. We used Western blotting to estimate that there are 200 to 400 TRAP 11-mer molecules per cell in cells grown in either minimal or rich medium.